Valuation of mortality risk attributable to climate change: investigating the effect of survey administration modes on a VSL - Sčasný, Milan; Alberini, Anna (International journal of environmental research and public health, 2012)
The health impact attributable to climate change has been identified as one of the priority areas for impact assessment. The main goal of this paper is to estimate the monetary value of one key health effect, which is premature mortality. Specifically, our goal is to derive the value of a statistical life from people's willingness to pay for avoiding the risk of dying in one post-transition country in Europe, i.e., the Czech Republic. We carried out a series of conjoint choice experiments in order to value mortality risk reductions. We found the responses to the conjoint choice questions to be reasonable and consistent with the economic paradigm. The VSL is about EUR 2.4 million, and our estimate is comparable with the value of preventing a fatality as used in one of the integrated assessment models. To investigate whether carrying out the survey through the internet may violate the welfare estimate, we administered our questionnaire to two independent samples of respondents using two different modes of survey administration. The results show that the VSLs for the two groups of respondents are €2.25 and €2.55 million, and these figures are statistically indistinguishable. However, the key parameters of indirect utility between the two modes of survey administration are statistically different when specific subgroups of population, such as older respondents, are concerned. Based on this evidence, we conclude that properly designed and administered on-line surveys are a reliable method for administering questionnaires, even when the latter are cognitively challenging. However, attention should be paid to sampling and choice regarding the mode of survey administration if the preference of specific segments of the population is elicited.
Keywords: Attitude; dospělí; průzkumy a dotazníky; hodnota života; chování snižující riziko; Climate Change; Female; Adult; klimatické změny; ženské pohlaví; Value of Life; Surveys and Questionnaires; lidé; postoj; sběr dat; Mortality, Premature; Risk Reduction Behavior; Male; Czech Republic; Data Collection; Choice Behavior; Internet; Česká republika; výběrové chování; lidé středního věku; mužské pohlaví; internet; Middle Aged; předčasná smrt; Humans